أحكام تأجير العين لمن باعها في صكوك الإجارة دراسة تحليلية نقدية في ضوء مقاصد الشريعة = Rulings on renting the property of those who sell it in leasing instruments: an analytical and critical study in the light of Maqāsid sharīʽah = Hukum penyewaan barangan bagi penjualnya dalam sukuk sewaan: kajian analisa kritikan menurut perspektif Maqāsid sharīʽah - Ghalia, Bouhedda; Bature, Habeeb (IIUM Press, International Islamic University Malaysia, 2018)
The issue of leasing the property of those who sell it is among the most significant issues that was raised in the rental instrument and is still being discussed currently. This is so because the instruments for leasing that includes another repeated rental procedure are like deeds with interest that the instruments of rental try to replace as a legitimate alternative. The substitute and the original in this case are of the same format. This prompts a study to look into the extent of compliance of its structure with the purposes of the Shari’ah in many of its forms. Through this study the purposeful view of the Shari’ah will emerge to help avoid from the suspicions of violating the Shari’a prohibitions that come with this issue. It would also help to reshape its structure and format that will comply with the Shari’ah in the fied of Mu’amalāt and fulfill the demands of the masses. ********************************************************* Isu penyewaan barangan bagi orang yang telah menjualnya-mengikut istilah sebahagian pengkaji- adalah antara masalah yang timbul dalam Sukuk Ijarah sejak kebelakangan ini. Ini kerana Sukuk Ijarah dengan penyewaan semula tidak ubah seperti sanad/ intrumen riba yang mana sukuk ijarah adalah antara alternatifnya yang patuh syariat. Dengan ini barang asal dan barang yang ditukar akan melalui satu aliran saja. Isu ini memerlukan kajian yang mendalam untuk membahaskan sejauh mana kerangkanya menepati maqasid syariah pada kebanyakan bentuk perlaksanaannya. Melalui kajian ini, kita akan menjelaskan pandangan maqasid yang membantu kita keluar dari syubhat perlanggaran syariat yang mungkin terjadi akibat isu ini. Selain itu, ia juga diharapkan membantu membina semula kerangkanya dalam bentuk yang bertepatan dengan syariat dan memenuhi tuntutan pelanggan.